Correlation between the corpus callosum form of people of the second period of adulthood and the craniometric parameters of the cerebral part of the skull - Boiagina, O. D. (Journal of Education, Health and Sport, 2017)
Objective. The goal is to establish how the form of the human corpus callosum depends on the craniometric parameters of the cerebral part of the skull. Methods. The material used was two samples from a series of head MR-tomograms of mentally healthy men and women aged from 32 to 60 years (the second period of adulthood) executed in the sagittal plane in the T1 and T2 modes of weighted images (5 mm thick). Results. As a result of the study, three main forms of corpus callosum were identified: low-convex, medium-convex and high-convex, which are directly dependent on the shape of the cerebral cranium. This dependence is determined on the basis of the proportional ratio of the corpus callosum length along the constricting chord to the longitudinal dimension of the cerebral cortex. The index of this ratio is 2.6, which allows to determine a person's rostrum-caudal size of a corpus callosum on the basis of the length of the brain cranium. This size does not correspond to the actual length of the corpus callosum, which can be calculated in approximate value by summing the lengths of the two thighs of its trunk convex. The metric ratio of this size does not directly depend on the length of the brain cranium, since it varies individually with a relative coefficient of 2.3.